1969
DOI: 10.2151/jmsj1965.47.3_219
|View full text |Cite
|
Sign up to set email alerts
|

Ice-forming Nuclei and Their Dominant Source Region

Abstract: The results of analysis of the data collected on the concentrations of the ice-forming and other forms of nuclei in a few places in India (Delhi, Calcutta, Bombay, Lonavla and Poona) have been presented.The ice-forming nuclei have varied generally inversely with the chloride nuclei at Delhi, Bombay and Poona.The ice-forming and hygroscopic nuclei have shown negative correlation at Delhi.The ice-forming and non-hygroscopic nuclei have varied on parallel lines at Poona.The relatively large value of the ice-formi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

1970
1970
1980
1980

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 20 publications
1
4
0
Order By: Relevance
“…The order of these concentrations was similar to those obtained earlier during the winter season at a coastal station, Calcutta, compared to a station well inland, Delhi. The ice-forming nuclei concentrations in this case, were 10.3 and 39.5 m-3, respectively, at Calcutta and Delhi (Kapoor et al, 1969). Also, the values were in agreement with 4536 4738 1643 1 1814 2419 2722 1663 2808 3024 29484 3578 4335 4687 3948 383 1 4032 2722 8115 4234 5743 the most comprehensive measurements on a global scale as reported by Bigg and Stevenson (1970).…”
Section: Chloride Iceforming and Total Nucleisupporting
confidence: 89%
See 1 more Smart Citation
“…The order of these concentrations was similar to those obtained earlier during the winter season at a coastal station, Calcutta, compared to a station well inland, Delhi. The ice-forming nuclei concentrations in this case, were 10.3 and 39.5 m-3, respectively, at Calcutta and Delhi (Kapoor et al, 1969). Also, the values were in agreement with 4536 4738 1643 1 1814 2419 2722 1663 2808 3024 29484 3578 4335 4687 3948 383 1 4032 2722 8115 4234 5743 the most comprehensive measurements on a global scale as reported by Bigg and Stevenson (1970).…”
Section: Chloride Iceforming and Total Nucleisupporting
confidence: 89%
“…Measurements on atmospheric aerosols at a few places in India reported earlier, suggested that the dominant source of ice-forming aerosols is land and that of hygroscopic aerosols is sea. These observations further indicated that the development of rain in coastal regions, at least in the tropics, is associated predominantly with a collision-coalescence process while in inland regions clouds do develop rain by ice-crystal mechanism as well (Ramana Murty et al, 1967;Kapoor et al, 1969Kapoor et al, , 1979. Simultaneous examination of ionic components in rain-water and aerosol state in different types of rain situations further suggested that the chemical state of air and precipitation activity are closely associated (Kapoor et al, 1972).…”
Section: Introductionmentioning
confidence: 96%
“…I n the previous studies reported (Ramana Murty et al, 1967;Kapoor et al, 1969) daily measurements have been made concurrently on the ice-forming and other forms of nuclei (hygroscopic and non-hygroscopic) by impaction techniques using Millipore filters and cascade impactors respectively, and inferences have been drawn on the basis that a substantial fraction of the hygroscopic nuclei measured originates from the sea while the non-hygroscopic nuclei originate from the land. I n the present investigation, which is limited only to rainy days, samples of rain water have been collected on the days of ice nuclei measurement which have been concurrently associated with rain and the soluble and the non-soluble components in the rain water, which respectively reflect the hygroscopic and the non-hygroscopic nuclei state of the air, have been studied.…”
Section: Methodsmentioning
confidence: 99%
“…However, more recent investigations (Kapoor et al, 1969) have suggested that the land is the dominant source region. The problem is examined further below in the light of other available data.…”
Section: Introductionmentioning
confidence: 99%
“…The order of these concentrations was similar to those obtained earlier during the winter season at a coastal station, Calcutta, compared to a station well inland, Delhi. The ice-forming nuclei concentrations in this case, were 10.3 and 39.5 m-3, respectively, at Calcutta and Delhi (Kapoor et al, 1969). Also, the values were in agreement with the most comprehensive measurements on a global scale as reported by Bigg and Stevenson (1970).…”
Section: Chloride Iceforming and Total Nucleimentioning
confidence: 99%